Earnings management and corporate tax planning and their impacts on firm value / Nik Mohd Norfadzilah Nik Mohd Rashid - Nik Mohd Rashid, Nik Mohd Norfadzilah (Institute of Graduate Studies, UiTM, 2017)
The research aimed to study the impacts of Earnings Management (EM) and Corporate Tax Planing (TP) on the changes of the Firm Value (FV) among public listed companies in Malaysia. Financial determinants of EM and Corporate TP which were both creative accounting strategies that formed the predictor variables, had first been identified. These were obtained from secondary data of 357 selected public listed companies from 2001 until 2012 retrieved from Thompson One Datastream database. Diagnostic analyses were performed to test normality and serial correlation of the data and obtain descriptive statistics including the analysis of variance for both EM and TP among the companies in the selected industries. Hence, in this study the measurement used for EM was related to the Accrual Earnings Management (AEM) and Real Earnings Management (REM) while the measurement for TP referred to accrual-based Effective Tax Rates (ETR1) and cash-based Effective Tax Rate (ETR2) level of the companies. Balance panel data of the selected companies within 12-year period produced 4,284 firm-year observation for further analyses determined by specification methods comprising Pooled Ordinary Least Squares, Fixed Effect and Random Effect regression analyses. The investigation were continued for the first phase of the study which related to the investigation of the financial determinants towards EM and Corporate TP among the companies. Results from the first phase initially disclosed that there was a significant relationship that existed between the selected financial transactions towards the EM and TP in the business transaction activities.